2023
DOI: 10.15376/biores.18.1.1637-1652
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional behavior of nail-laminated timber-concrete composite caused by changes in ambient air, and correlation among temperature, relative humidity, and strain

Abstract: A timber-concrete composite (TCC) slab composed of nail-laminated timber (NLT) and topping concrete (TC) was developed for flooring applications. The NLT was laminated alternately with lumber and plywood. To investigate the nonstructural dimensional behavior of the TCC slab, the temperature, relative humidity (RH), and dimensional changes of the slab exposed to outdoor air were monitored for 205 days. Temperature change was transmitted directly to both components, and RH change was transmitted gradually to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hwang et al [91] reported the moisture content (MC) of the NLT-concrete composite floor exposed to outdoor environments. It was found that the MC of NLT increased with the increase in the ambient RH and the pouring of wet concrete.…”
Section: Methodsmentioning
confidence: 99%
“…Hwang et al [91] reported the moisture content (MC) of the NLT-concrete composite floor exposed to outdoor environments. It was found that the MC of NLT increased with the increase in the ambient RH and the pouring of wet concrete.…”
Section: Methodsmentioning
confidence: 99%
“…Three or more consecutive points within a distance of 0.1 from a data point are considered a cluster. Hwang et al (2023). "Moisture of biomass feedstocks," BioResources 18(1), 2064-2082.…”
Section: Clusteringmentioning
confidence: 99%
“…As with the MC measurements, the increase in bulk density contributed to the creation of continuous paths for charge travel. Hwang et al (2023). "Moisture of biomass feedstocks," BioResources 18(1), 2064-2082.…”
Section: Electrical Resistancementioning
confidence: 99%
See 1 more Smart Citation